PENERAPAN PRINSIP DESAIN KOMUNIKASI VISUAL PADA INSTAGRAM @kpudiy GUNA MEMENUHI KEBUTUHAN INFORMASI - Andre Ade Syaputra; Angga Intueri Mahendra (LPPM Institut Pendidikan Nusantara Global, 2023)
The importance of Instagram as a social media that is useful as a platform for spreading information and communication. The effectiveness of the dissemination of information and communication is certainly influenced by the content posted on Instagram. This is of course related to content criteria that match the audience on social media Instagram. This study discusses the application of design principles to Instagram kpu diy. This study aims to determine the application of existing design principles to content on Instagram by the General Election Commission of the Special Region of Yogyakarta as an information center for the community. This research was analyzed by theoretical and empirical studies, then described and interpreted based on the research results. The population in this study uses the DIY KPU Instagram feed design. The sample in this study uses a simple random sampling technique, namely choosing a design that is less relevant or in accordance with existing design principles. The results of research on this design can be described based on an analysis of some of the content that is not in accordance with the principles of graphic design which will then be related to the information conveyed to the audience whether it meets the information needs of the readers. The results of this study can be concluded that the Diy KPU's Instagram found some content that was not in accordance with design principles, and also information about elections that was conveyed on the Diy KPU's content was mostly covered with internal KPU DIY information